Exploring Differentiated Content in EFL Teaching Modules by Pre-service Teachers - Maryani; Endang Setyaningsih; Nur Arifah Drajati (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
The increasing diversity of students’ learning characteristics brought a growing challenge for teachers to provide accessible and inclusive learning. This research explored the differentiated content portrayed in pre-service EFL teachers’ teaching modules, including their decisions in designing and selecting content for differentiation. A qualitative case study was conducted, involving five pre-service English as a Foreign Language (EFL) teachers who participated in a teacher education program. This research gleaned the data through document analysis and interviews, which then exhibited that the content differentiation was presented through the use of diagnostic assessment as pre-assessment for content adaptation, different teaching materials, and a variety of teaching modes tailored to students’ learning profiles. Moreover, pre-service EFL teachers reported that they considered students’ abilities, readiness, learning profiles, curriculum demands, sociocultural background, and available resources when designing and choosing content for differentiation. These findings emphasized the pre-service EFL teachers’ awareness of diverse learners and their efforts to plan their instruction accordingly. This research offers insight into how future teachers prepare for differentiated instruction in an EFL setting.